Robotic Surgery in Gynecologic Oncology - Robert DeBernardo; David Starks; Nichole Barker; Amy Armstrong; Charles A. Kunos (Hindawi Limited, 2011)
Robotic surgery for the management of gynecologic cancers allows for minimally invasive surgical removal of cancer-bearing organs and tissues using sophisticated surgeon-manipulated, robotic surgical instrumentation. Early on, gynecologic oncologists recognized that minimally invasive surgery was associated with less surgical morbidity and that it shortened postoperative recovery. Now, robotic surgery represents an effective alternative to conventional laparotomy. Since its widespread adoption, minimally invasive surgery has become an option not only for the morbidly obese but for women with gynecologic malignancy where conventional laparotomy has been associated with significant morbidity. As such, this paper considers indications for robotic surgery, reflects on outcomes from initial robotic surgical outcomes data, reviews cost efficacy and implications in surgical training, and discusses new roles for robotic surgery in gynecologic cancer management.